In Vitro Study of Biocontrol Potential of Rhizospheric Pseudomonas aeruginosa against Pathogenic Fungi of Saffron (Crocus sativus L.) - Shuang Hu (MDPI AG, 2021)
Plant rhizosphere soil contains a large number of plant-growth promoting rhizobacteria, which can not only resist the invasion of pathogenic microorganisms and protect plants from damage, but also promote the growth and development of plants. In this study, Pseudomonas aeruginosa strain YY322, isolated and screened from the rhizosphere soil of saffron (Crocus sativus L.), was found through a plate confrontation experiment to show highly effectual and obvious antagonistic activity against the pathogens of saffron, including Fusarium oxysporum, Fusarium solani, Penicillium citreosulfuratum, Penicillium citrinum and Stromatinia gladioli. In addition, the volatile organic compounds of strain YY322 had great antagonistic activity against these pathogens. Observation under a scanning electron microscope and transmission electron microscope reflected that strain YY322 had a significant effect on the hyphae and conidia of F. oxysporum and F. solani. Through the detection of degrading enzymes, it was found that P. aeruginosa can secrete protease and glucanase. The plant growth promoting performance was evaluated, finding that strain YY322 had the functions of dissolving phosphorus, fixing nitrogen, producing siderophore and producing NH3. In addition, whole genome sequencing analysis indicated that the YY322 genome is comprised of a 6,382,345-bp circular chromosome, containing 5809 protein-coding genes and 151 RNA genes. The P. aeruginosa YY322 genome encodes genes related to phenazine (phzABDEFGIMRS), hydrogen cyanide(HCN) (hcnABC), surfactin (srfAA), salicylate (pchA), biofilm formation (flgBCDEFGHIJKL, motAB, efp, hfq), and colonization (minCDE, yjbB, lysC). These results collectively indicated the role of P. aeruginosa YY322 in plant growth enhancement and biocontrol mechanisms. All in all, this study provides a theoretical basis for P. aeruginosa as the PGPR of saffron, paving the way for the subsequent development and utilization of microbial fertilizer.